NUTRITIVE AND ANTI-NUTRITIONAL VALUES OF SKINNED EDIBLE BULLFROG PYXICEPHALUS ADSPERSUS FOR AQUAFEED - Udeh, L. O.; Auta, J.; Bawa, Bolanle S.; Galadima, M. I. (FUDMA JOURNAL OF SCIENCES, 2024)
An investigation on proximate, mineral and anti-nutrition properties of Pyxicephalus adspersus was conducted with the view to evaluating its appropriateness as aquafeed source and food source. Standard analytical methods were used to determine proximate, minerals (macro and micro nutrients) and selected anti-nutrients. Pyxicephalus adspersus samples were purchased and treated to skinning and oven drying at 60oC. Triplicate samples were analysed. The proximate composition showed crude protein content of 34.29%, ash 8.18%, while dry matter, moisture, crude fibre, crude lipid, and NFE were 93.12%, 5.60%, 11.82%, 16.79% and 22.04%, respectively. Pyxicephalus adspersus was found to have values (mg/100g) of phosphorus 29.20, calcium 10.60, potassium 4.52, sodium 1.50, and magnesium 1.28. Anti-nutritional compositions (mg/100g) were 5.40, 2.68, 2.06, and 3.05 for tannin, oxalate, saponin and alkaloid, respectively. This result shows that Pyxicephalus adspersus could be used as protein source in meeting aquafeed standard without adverse effects. The crude protein (34.20%) content can be used to substitute the most expensive fishmeal in aquafeed and livestock. Also, the carbohydrate content of 22.04% suggests that it is a good source of energy.
Keywords: Anti-nutrients; Mineral content; Nutritional content; Pyxicephalus adspersus